Accounting Theory and Its Effective Role in Developing Intellectual and Mental Skills and Abilities Of Accounting Department Students: a Field Study - Sadiq Jafar Kathim; Layla Naji Majeed Al Fatlaw; Qasim Mohammed Abdullah Al-Baaj (International Forum of Researchers and Lecturers, 2024)
The research aims to shed light on the role of accounting theory as one of the main subjects that have an active role in the intellectual skills and abilities of the students of the Department of Accounting and to provide a theoretical framework linking the subject of accounting theory and the intellectual skills and abilities of the students of the Department of Accounting and to indicate the relationship of correlation and influence between the subject of accounting theory and the intellectual skills and abilities of students of the Department of Accounting, and to provide recommendations and proposals to the organisation of the research sample regarding the subject of teaching accounting theory and its active role in the intellectual skills and abilities of students of the Department Accounting, the deductive and inductive approach was adopted in dealing with the research problem and proving its hypotheses in the theoretical aspect to achieve the objectives of the research and relying on the descriptive approach in the practical aspect, The research sample was represented by the students of the Department of Accounting at the College of Administration and Economics - University of Al-Qadisiyah for the year 2024, a questionnaire form was designed and distributed to the research sample and then collected and analysed statistically for the purpose of proving the research hypotheses and achieving the results The research reached a set of conclusions, the most important of which is the information that there is a statistically significant correlation between accounting theory and the intellectual skills and abilities of students of the accounting department The strength of the correlation is characterised by being very strong and its value is (.636**), which is at a lower moral level From (0.01), which confirms the positive correlation of this research, the existence of a significant effect between the variables of the research and the value of the regression coefficient was (β) (.636), which confirms the positive impact of this research, and therefore the study recommends a set of recommendations, the most important of which is the development of the accounting theory approach adopted in the accounting department so that it is able to keep pace with the continuous development known by the reality of the profession, which enables the accountant to perform his tasks better and understand how to teach accounting theory in decision-making processes.